2004
DOI: 10.1099/jmm.0.05315-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular identification of Candida dubliniensis from non-human immunodeficiency virus-infected patients in Kuwait

Abstract: Candida dubliniensis is an emerging pathogen capable of causing oropharyngeal, vaginal and bloodstream infections. Although C. dubliniensis is similar to Candida albicans in several phenotypic characteristics, it differs from it with respect to epidemiology, certain virulence factors and the ability to develop resistance to fluconazole rapidly. In this study, the first seven isolations of C. dubliniensis from Kuwait are described, all originating from non-human immunodeficiency virus (HIV)-infected patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 23 publications
3
57
0
1
Order By: Relevance
“…horizontal shaking for 24-48 h at 35 uC. T. asahii strains were first identified via VITEK-2 Compact with YST cards, and then verified through DNA sequencing of the internal transcribed spacer (ITS) locus of the rDNA, using primers ITS1/ITS4 (ITS1 : 59-TCCGTAGGTGAACCTGCGG-39; ITS4 : 59-TCCTCCGC-TTATTGATATGC-39) (Ahmad et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…horizontal shaking for 24-48 h at 35 uC. T. asahii strains were first identified via VITEK-2 Compact with YST cards, and then verified through DNA sequencing of the internal transcribed spacer (ITS) locus of the rDNA, using primers ITS1/ITS4 (ITS1 : 59-TCCGTAGGTGAACCTGCGG-39; ITS4 : 59-TCCTCCGC-TTATTGATATGC-39) (Ahmad et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…However, two recent studies reported that 18/32 (56%) and 2/7 (29%) C. dubliniensis isolates tested from Saudi Arabia (17) and Kuwait (1), respectively, were 5FC resistant (MIC Ͼ 32 g/ml). On the basis of the results of the present study, it is interesting to speculate that the 5FC-resistant C. dubliniensis isolates described by Fotedar and Al Hedaithy (17) and Ahmad et al (1) may also belong to the CD25 group III clade. In support of this suggestion, a recent study demonstrated that 5FC resistance in C. albicans is restricted to a single genetic clade (38).…”
Section: Discussionmentioning
confidence: 91%
“…There have been several reports describing the recovery of C. dubliniensis isolates in a variety of Middle Eastern countries (1,17,18,26), but little is known about the population structure or the epidemiology of these isolates or their relationship to isolates recovered in the rest of the world. Gee et al (18) included eight independent isolates of C. dubliniensis recovered in Israel in their study, four of which belonged to Cd25 group I (genotype 1), with the other four belonging to Cd25 group II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. dubliniensis, the resistance patterns are more clearly defined, with 5FC-susceptible isolates exhibiting 5FC MICs of Յ0.125 g/ml and 5FC-resistant isolates exhibiting 5FC MICs of Ն128 g/ml (4). To date, 5FC resistance in C. dubliniensis has been reported only in isolates from the Middle East, all of which that have been tested belong to MLST clade C3 (1,4,18,29).…”
mentioning
confidence: 99%